Gallbladder volvulus - Antiga, E.; Chavarria, O.; Grezzi, R. (Cirugía del Uruguay, 1971)
Three cases of torsion of the gall bladder are repported. Two were acute torsions and the other one was probably a case of recidivant torsion. Emphasis is made on the urgency of the opperation as in any other acute situation of the right abdomen.